Moringaoliefera Coagulator: A New Fighter to Combat with Water Pollution: Investigating the use of Moringaoliefera as a local coagulating material for improving groundwater quality (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Groundwater is the most important natural resource used for drinking by many people around the world, especially in arid and semi-arid areas. The resource cannot be optimally used and sustained unless the quality of groundwater is assessed. The Proposed study is to determine the suitability of Moringaoliefera as an alternative and cheap local coagulating material in the improvement of water quality in terms of turbidity, pH, and colour and microorganism removal for Firozabad. This study also illustrates the qualitative analysis of groundwater and its suitability in the bulk samples collected from different canal catchment areas. This study suggested that groundwater is unsafe for drinking purpose without purification and quality measures should be considered while cropping in its irrigation use.